The PERAN CANDI PRAMBANAN DAN BOROBUDUR SEBAGAI TEMPAT ACARA DALAM MENDUKUNG ACARA BERKELANJUTAN - Octavanny, Vitha; Ayu, Jati Paras; Prabowo, Riky Ramadani; Wibowo DC, Yesi Pandu Pratama (ASEAN Journal on Hospitality and Tourism, 2024)
Prambanan Temple and Borobudur Temple, managed by PT Taman Wisata Candi, play a crucial role in implementing these venue indicators, as they are key providers of event venues at local, national, and international levels. This research employs qualitative research methods with descriptive analysis approach, including interviews with stakeholders at PT Taman Wisata Candi involved in event management. The aim is to understand the role of temple management in supporting sustainable events as a venue provider. The findings indicate that the management has followed the principles of sustainable event management, focusing three socio-cultural elements of the environment broadly categorized under “Tanggung Jawab Sosial Lingkungan” (TJSL), or Environmental Socio Responsibility. This program aims to support all activities at PT Taman Wisata Candi. However, certain aspects need to be concidered to minimize negative impacts during events at Prambanan and Borobudur Temples. To accomplish this, it is necessary to strengthen the event management process by providing supporting documents, such as the development of Standard Operating Procedures (SOPs) for post-event activity reporting related to sustainable event indicators, as well as the creation of guidebooks detailing the objectives of the nine indicators. These indicators cover aspects such as planning, policy formulation, monitoring, and evaluation following the Event Industry Council’s approach to sustainable events.